LINGKUNGAN PENDIDIKAN MENURUT AL-QUR’AN - Zulhammi, Zulhammi (AIN Padangsidimpuan, 2014)
AbstractThe Environment of education is not described in the Qur'an explicitly, but there are several signs that indicate the presence of the educational environment The family is the first educational environment where children get an education. At this point in the family laid the foundations of a child's personality. TheSchool as second in environment that developing the potential environmental grounds owned by the child. School is an environment where students absorb academic values including socializing with teachers and school friends. The Society is an educational institution after family and school. The shades of various education received by students in the community, covering all areas of both habit formation, the formation of knowledge, attitudes, interests, and the establishment of morality and religion. The natural environment is also used as a source of learning.